Bodies as evidence: Mapping new terrain for teen pregnancy and parenting. Issue 5 (2nd July 2016) - Gubrium, Aline C.; Fiddian-Green, Alice; Jernigan, Kasey; Krause, Elizabeth L.
ABSTRACT: Predominant approaches to teen pregnancy focus on decreasing numbers of teen mothers, babies born to them, and state dollars spent to support their families. This overshadows the structural violence interwoven into daily existence for these young parents. This paper argues for the increased use of participatory visual methods to compliment traditional research methods in shifting notions of what counts as evidence in response to teen pregnancy and parenting. We present the methods and results from a body mapping workshop as part of 'Hear Our Stories: Diasporic Youth for Sexual Rights and Justice', a project that examines structural barriers faced by young parenting Latinas and seeks to develop relevant messaging and programming to support and engage youth. Body mapping, as an engaging, innovative participatory visual methodology, involves young parenting women and other marginalised populations in drawing out a deeper understanding of sexual health inequities. Our findings highlight the ways body mapping elicits bodies as evidence to understand young motherhood and wellbeing.